Neoadjuvant apatinib addition to sintilimab and carboplatin-taxane based chemotherapy in patients with early triple-negative breast cancer: the phase 2 NeoSAC trial - Guoshuang Shen; Zhilin Liu; Miaozhou Wang; Yi Zhao; Xinlan Liu; Yujin Hou; Wenbiao Ma; Jingqi Han; Xiaofeng Zhou; Dengfeng Ren; Fuxing Zhao; Zitao Li; et al. (Signal Transduction and Targeted Therapy)
Abstract We aimed to evaluate the efficacy and safety of adding apatinib, to sintilimab and chemotherapy in the neoadjuvant treatment of early triple-negative breast cancer (TNBC). In the phase 2 NeoSAC trial, patients with early TNBC received six cycles of apatinib, sintilimab, nab-paclitaxel, and carboplatin followed by surgery. The primary endpoint was pathological complete response (pCR) rate. Specimens collected pre-neoadjuvant therapy and post-surgery were retained for comprehensive analysis of predictive biomarkers and the impact on the tumor microenvironment. Among 34 enrolled patients, 24 achieved pCR (70.6%; 95% confidence interval (CI), 53.0-85.3), and 79.4% (95% CI, 65.1-93.7) had residual cancer burden 0-I. Imaging evaluation showed 21 complete responses (61.8%) and 13 partial responses (38.2%). The most common grade 3-4 adverse events were leukopenia (47%), neutropenia (36%), and thrombocytopenia (24%). The 36-month disease-free survival rate stood at 94.1% with a median follow-up of 39.1 months. Notably, baseline high ImmuneScore, immune cell infiltration, and enrichment of interferon-related pathways correlated with pCR. Comparison of pre-neoadjuvant and post-surgery data revealed that the pCR group treated with this novel regimen exhibited an upregulation of distinct immune cell subsets, thereby activating the tumor microenvironment. Moreover, higher oxeiptosis scores were associated with an increased likelihood of achieving pCR. Following neoadjuvant therapy, the pCR group showed a decrease in oxeiptosis score, whereas the non-pCR group exhibited an increase. Our study suggests that apatinib, sintilimab combined with carboplatin and nab-paclitaxel chemotherapy showed a promising clinical activity and manageable safety profile in early TNBC and merits further study. ClinicalTrials.gov registration: NCT04722718.